toner
The toner with convex organosilicon polymer portions on its surface addresses the challenge of maintaining high transferability at low biases, enhancing the efficiency and longevity of electrophotographic image forming devices.
Patent Information
- Application Number
- JP2020175016
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-16
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2040-10-16
AI Technical Summary
Existing toners struggle to maintain high transferability over time and at low transfer biases, leading to inefficiencies in electrophotographic image forming apparatuses, which hinders their miniaturization.
A toner with toner base particles having a plurality of convex portions containing an organosilicon polymer on the surface, where the convex portions have specific dimensions and ratios, enhancing transferability by reducing adhesion and maintaining charge stability.
The toner achieves high transferability even at low transfer biases, ensuring stable performance over time and contributing to the downsizing of electrophotographic image forming apparatuses.
Smart Images

Figure 0007604165000006 
Figure 0007604165000007 
Figure 0007604165000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner used in an image forming method such as an electrophotographic method. [Background technology]
[0002] Electrophotographic image forming apparatuses are required to have higher image quality, longer life, and smaller size, and in order to meet these demands, toners are also required to have improved performance in various ways.
[0003] From the viewpoint of miniaturization of an electrophotographic image forming apparatus, attempts have been made to miniaturize various units constituting the electrophotographic image forming apparatus. In particular, since the improvement of the transferability of toner allows the size of a waste toner container for collecting the transfer residual toner on the photosensitive drum to be reduced, attempts have been made to improve the transferability of various toners.
[0004] In the transfer process, the toner developed on the photosensitive drum is transferred to a medium such as paper. In order to improve the transferability of the toner, it is important to reduce the adhesive force between the photosensitive drum and the toner so that the toner can be easily separated from the photosensitive drum. One method for reducing the adhesive force between the photosensitive drum and the toner is to attach an external additive to the surface of the toner particles. In particular, a method is known in which the physical adhesive force between the photosensitive drum and the toner is reduced and the transfer efficiency is improved by the spacer effect of adding a large-diameter spherical external additive. However, although this method is an effective technology for improving the transfer efficiency, the large-diameter spherical external additive moves, detaches, or is buried on the surface of the toner particles due to long-term image output, and is therefore unable to function as a spacer. Therefore, it was difficult to stably obtain the expected effect of improving the transfer efficiency with this method.
[0005] In view of this, a method has been proposed in which the large particle diameter external additive is semi-embedded in the surface of the toner particles to suppress the movement and detachment of the large particle diameter external additive (see Patent Document 1). Although this method can suppress the movement and detachment of the large particle diameter external additive from the surface of the toner particles, it has the problem of accelerating the embedding of the large particle diameter external additive.
[0006] Meanwhile, a method has been proposed in which a large-diameter external additive having a hemispherical shape is used to suppress the detachment and embedment of the large-diameter external additive on the toner particle surface (see Patent Document 2). However, with this method, it is difficult to uniformly fix the large-diameter external additive to the toner particle surface, making it difficult to maintain the effect of improving transfer efficiency in response to further extending the life of the toner.
[0007] Therefore, a method of using a large particle size external additive in combination with a silane coupling agent has been proposed (see Patent Document 3). This method makes it possible to control the roughness of the toner particle surface while fixing the large particle size external additive to the toner particle surface with the silane coupling agent. As a result, it is possible to suppress the movement, detachment, or embedding of the large particle size external additive on the toner particle surface, and it has become possible to achieve high transferability over a long period of time.
[0008] As a further technology, if it is possible to maintain excellent transferability even when the transfer bias is lowered, the power supply unit can be made smaller, which leads to further miniaturization of the electrophotographic image forming apparatus. Therefore, there is a demand for a toner that can maintain good transferability even at a low transfer bias. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent Application No. 2009-36980 [Patent Document 2] Patent No. 5223382 [Patent Document 3] JP 2017-138462 A Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a toner that solves the above problems. Specifically, the object is to provide a toner capable of maintaining excellent transferability even with a low transfer bias throughout durability. [Means for solving the problem]
[0011] The present invention provides a toner having a toner base particle and a plurality of convex portions X present on the surface of the toner base particle, the protruding portion X contains an organosilicon polymer, In cross-sectional observation of the toner using a scanning transmission electron microscope (STEM), When the maximum line segment at the continuous interface between the convex portion X and the toner base particle is defined as a convex width w, and the maximum length of the convex portion X in the normal direction of the convex width w is defined as a convex height H, and among the multiple convex portions X, a convex portion X having a convex height H of 40 nm or more is defined as a convex portion Y, the ratio P(H / w) of the number of the protrusions Y in which the ratio (H / w) of the protrusion height H to the protrusion width w is 0.33 or more and 0.80 or less is 70% by number or more with respect to the total number of the protrusions Y; a migration rate of the protrusions X in a water washing method of the toner is 5% by number or more and 20% by number or less of the entire protrusions X before washing with water, The toner is characterized in that the number average particle diameter D1 of the protrusions X transferred into water by the water washing method is 30 nm or more and 300 nm or less. Effect of the Invention
[0012] According to the present invention, it is possible to provide a toner that exhibits high transferability even when a transfer bias is low, is less likely to change over time, and is capable of maintaining high transferability. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a schematic diagram of an example of cross-sectional observation of the toner of the present invention by STEM. [Diagram 2] FIG. 2 is a schematic diagram of an example of measuring a convex shape of a toner according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In order to improve the transfer efficiency, it is effective to reduce the adhesive force between the photosensitive drum (hereinafter also simply referred to as "drum") and the toner. For this reason, it is important to control the surface structure of the toner particles, and the transferability has been improved by the above-mentioned conventional technology. However, in recent years, when further miniaturization of electrophotographic image forming apparatuses is required, there is a demand for technology that maintains good transferability even when the transfer bias is lowered. Therefore, the present inventors have studied technology for maintaining excellent transferability even when the transfer bias is lowered.
[0015] The relationship between the toner and the drum before transfer is such that the toner is electrically and physically attached to the drum. By applying a transfer bias to this state, the toner is electrically attracted to the transfer media and transfer is performed. Therefore, if the transfer bias is low, the toner cannot move due to the attractive force between the toner and the photoreceptor, and there is a lot of residual toner after transfer. Many of the conventional technologies, such as large particle size external additives, have focused on reducing the physical adhesion force, but it was difficult to reduce the electrical adhesion force as well. The reason for this is that the electrical adhesion force is generated by the toner being charged, and it is essential to charge the toner in order to develop the toner on the drum in the process before transfer. In addition, it was difficult with the conventional technology to conveniently attenuate the charge after passing through the development process. Therefore, if we could create a technology that maintains a high charge when developing the toner on the drum and attenuates the charge after it is developed on the drum, we thought that we could achieve transfer with a low transfer bias, which was difficult to achieve in the past.
[0016] The present inventors have investigated techniques for reducing the charge of the toner on the drum, focusing on the charge order of various substances. As a result, they have found that by performing transfer in a state where particles with a higher charge amount than the toner are present on the drum, the toner can maintain good transferability even when the transfer bias is lowered. In particular, it is particularly effective to perform transfer in a state where organosilicon polymer particles of a specific particle size are present on the drum.
[0017] The mechanism is believed to be as follows. The electrostatic charge sequence of organosilicon polymers is superior to that of Teflon (registered trademark), and they have the property of being easily charged negatively. When this is added separately from the toner and placed in a situation where it rubs against the toner, the organosilicon polymer particles tend to be more negatively charged, which tends to reduce the chargeability of the toner. It is believed that reducing the toner's inherent electrostatic charge reduces the electrical adhesive force between the toner and the drum, and the toner is able to maintain good transferability even when the charging bias is reduced.
[0018] Here, a means for making the organosilicon polymer exist on the drum is necessary. As a means for this, it was considered to make the organosilicon polymer that easily migrates to the drum exist on the surface of the toner base particles and to make it migrate to the drum during development. It was considered that by doing so, the organosilicon polymer can contribute to both excellent charging properties and transfer properties. In other words, since the organosilicon polymer has a negative chargeability superior to Teflon (registered trademark), if it exists on the surface of the toner base particles during development, it can contribute to the good charging properties of the toner. And, if the organosilicon polymer is migrated to the drum side after development on the drum, it can contribute to the good transfer properties of the toner. In other words, it was considered that if the organosilicon polymer that easily migrates to the drum exists on the surface of the toner base particles, both of these effects can be achieved. Conventionally, the main technology was from the viewpoint of how to prevent the external additives present on the surface of the toner base particles from coming off the toner, so there was no study on actively moving the material of the surface of the toner base particles or the external additives to the drum.
[0019] The toner of the present invention is a toner having toner particles having a toner base particle and a plurality of convex portions X present on the surface of the toner base particle, and the convex portions X contain an organosilicon polymer, which provides good charging characteristics and improves transferability due to improved fluidity.
[0020] Furthermore, the toner particles of the present invention have a plurality of protrusions X containing an organosilicon polymer present on the surface of a toner base particle, and when cross-sectional observation of the toner by STEM reveals that when the maximum line segment at the continuous interface of the protrusions X with the toner base particle is taken as the protrusion width w, and the maximum length of the protrusions X in the normal direction to the protrusion width w is taken as the protrusion height H, and when the protrusions X among the plurality of protrusions X have a protrusion height H of 40 nm or more as protrusion Y, the proportion P(H / w) of the number of protrusions Y where the ratio (H / w) of the protrusion height H to the protrusion width w is 0.33 or more and 0.80 or less is 70% by number or more of the total protrusions Y.
[0021] This is believed to be because the convex portion X creates a spacer effect between the surface of the toner base particle and the drum, which reduces the adhesive force between the toner and the drum, improving transferability. On the other hand, as the convex height H increases, the surface of the toner particle is more susceptible to force, but the convex portion X of the present invention is characterized by being in surface contact with the surface of the toner base particle, and surface contact is expected to have a significant effect of suppressing the embedding of the organosilicon polymer of the convex portion X into the toner base particle. In order to show the degree of surface contact, a cross-section of the toner was observed using STEM. Figure 1 shows a STEM image. 1 is a STEM image, in which about 1 / 4 of the toner particle can be seen, 2 is a toner base particle, 3 is the surface of the toner base particle, 4 is a convex portion X, and 5 is a convex portion Y. Figure 2 shows an example of the convex portion X on the surface of a toner particle. 6 is the convex width w, and 7 is the convex height H. It was found that if the convex shape has a ratio (H / w) of the convex height H to the convex width w of 0.33 to 0.80, the toner is less likely to be embedded. That is, it was found that the convex portions of the organosilicon compound are less likely to be buried if they have a convex shape as shown in Fig. 2. In addition, it was found that if, in the convex portions Y having a convex height H of 40 nm or more, the ratio of the convex height H to the convex width w (H / w) is 0.33 or more and 0.80 or less, the number ratio P(H / w) of the convex portions is 70% or more relative to the total number of the convex portions Y, this is a requirement for the toner of the present invention to exhibit excellent transferability capable of withstanding a long life.
[0022] Furthermore, the toner of the present invention requires that the migration rate of the convex portion X in the water washing method of the toner is 5% by number or more and 20% by number or less of the total of the convex portion X before washing. Furthermore, the number average particle diameter D1 of the convex portion X that has migrated into water by the water washing method must be 30 nm by number or more and 300 nm by number or less. When the migration rate is 5% by number or more, the organosilicon polymer present on the surface of the toner base particle migrates to the drum side, and the toner can maintain excellent transferability even when the transfer bias is lowered. On the other hand, if the migration rate is 20% by number or less, it is possible to supply the necessary number of organosilicon polymer particles to the drum side during durability, so that it is possible to maintain excellent transferability throughout durability. When the number average particle diameter D1 of the convex portion X is 30 nm or more, it can be triboelectrically charged independently of the toner, so that the chargeability of the toner can be reduced, and even when the transfer bias is lowered, the toner can maintain excellent transferability. On the other hand, if the particle size is too large, the fluidity decreases, so that it is preferable for the particle size to be 300 nm or less for excellent transferability.
[0023] In a more preferable case, the number average particle diameter D1 is 50 nm or more and 300 nm or less, and the ratio D1 / D2 of the number average particle diameter D2 of the convex portion X that migrates into the water when the toner after the washing method is washed again is preferably 1.0 or more and 5.0 or less. If the number average particle diameter D1 is this particle diameter, spacers are provided on both the drum and the toner, and particularly excellent transferability is obtained. In addition, D1 / D2 being 1.0 or more and 5.0 or less means that the organosilicon polymer particles with a larger particle diameter migrate to the drum side. If the particle diameter of the organosilicon polymer that migrates to the drum side is small, the particles may be buried between the convex portions X of the toner particles and may not rub against the toner sufficiently. D1 / D2 being 1.0 or more is preferable because the toner and the organosilicon polymer particles can be sufficiently rubbed. On the other hand, if D1 / D2 is too large, the fluidity decreases, so it is preferable for D1 / D2 to be 5.0 or less for excellent transferability.
[0024] In the toner of the present invention, an organosilicon polymer having a structure represented by the following formula (1) is preferably used.
number
[0025] In an organosilicon polymer having the structure of formula (1), one of the four valences of the Si atom is bonded to R, and the remaining three are bonded to O atoms. The O atom has two valences bonded to Si, that is, it forms a siloxane bond (Si-O-Si). When considering the Si atom and O atom as an organosilicon polymer, there are two Si atoms and three O atoms, so -SiO 3 / 2 This organosilicon polymer is expressed as -SiO 3 / 2 The structure is thought to have similar properties to silica (SiO2), which is composed of numerous siloxane bonds.
[0026] In the partial structure represented by formula (1), R is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms.
[0027] Preferred examples of the alkyl group having 1 to 3 carbon atoms include a methyl group, an ethyl group, and a propyl group. More preferably, R is a methyl group.
[0028] The organosilicon polymer is preferably a condensation polymer of an organosilicon compound having a structure represented by the following formula (Z).
number
[0029] R1 is preferably an aliphatic hydrocarbon group having 1 to 3 carbon atoms, and more preferably a methyl group.
[0030] R2, R3, and R4 are each independently a halogen atom, a hydroxyl group, an acetoxy group, or an alkoxy group (hereinafter also referred to as a reactive group). These reactive groups undergo hydrolysis, addition polymerization, and condensation polymerization to form a crosslinked structure.
[0031] From the viewpoint of mild hydrolysis at room temperature and deposition onto the surface of the toner base particles, an alkoxy group having 1 to 3 carbon atoms is preferable, and a methoxy group or an ethoxy group is more preferable.
[0032] The hydrolysis, addition polymerization, and condensation polymerization of R2, R3, and R4 can be controlled by the reaction temperature, reaction time, reaction solvent, and pH. To obtain the organosilicon polymer used in the present invention, it is advisable to use one or a combination of several organosilicon compounds (hereinafter also referred to as trifunctional silanes) having three reactive groups (R2, R3, and R4) in one molecule excluding R1 in the formula (Z) shown above.
[0033] Examples of the compound represented by the above formula (Z) include the following. Trifunctional methylsilanes such as methyltrimethoxysilane, methyltriethoxysilane, methyldiethoxymethoxysilane, methylethoxydimethoxysilane, methyltrichlorosilane, methylmethoxydichlorosilane, methylethoxydichlorosilane, methyldimethoxychlorosilane, methylmethoxyethoxychlorosilane, methyldiethoxychlorosilane, methyltriacetoxysilane, methyldiacetoxymethoxysilane, methyldiacetoxyethoxysilane, methylacetoxydimethoxysilane, methylacetoxymethoxyethoxysilane, methylacetoxydiethoxysilane, methyltrihydroxysilane, methylmethoxydihydroxysilane, methylethoxydihydroxysilane, methyldimethoxyhydroxysilane, methylethoxymethoxyhydroxysilane, and methyldiethoxyhydroxysilane. Trifunctional silanes such as ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrichlorosilane, ethyltriacetoxysilane, ethyltrihydroxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltrichlorosilane, propyltriacetoxysilane, propyltrihydroxysilane, butyltrimethoxysilane, butyltriethoxysilane, butyltrichlorosilane, butyltriacetoxysilane, butyltrihydroxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, hexyltrichlorosilane, hexyltriacetoxysilane, and hexyltrihydroxysilane. Trifunctional phenylsilanes such as phenyltrimethoxysilane, phenyltriethoxysilane, phenyltrichlorosilane, phenyltriacetoxysilane, and phenyltrihydroxysilane.
[0034] In addition, to the extent that the effect of the present invention is not impaired, an organosilicon polymer obtained by combining the following with an organosilicon compound having a structure represented by formula (Z) may be used. An organosilicon compound having four reactive groups in one molecule (tetrafunctional silane), an organosilicon compound having two reactive groups in one molecule (bifunctional silane), or an organosilicon compound having one reactive group (monofunctional silane). For example, the following may be mentioned. Trifunctional vinyl silanes such as dimethyldiethoxysilane, tetraethoxysilane, hexamethyldisilazane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, vinyltriisocyanatesilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyldiethoxymethoxysilane, vinylethoxydimethoxysilane, vinylethoxydihydroxysilane, vinyldimethoxyhydroxysilane, vinylethoxymethoxyhydroxysilane, and vinyldiethoxyhydroxysilane.
[0035] Furthermore, the content of the organosilicon polymer in the toner particles is preferably from 1.0% to 10.0% by weight.
[0036] A preferred method for forming the convex shape containing the specific organosilicon polymer according to the present invention on the surface of the toner base particles is to disperse the toner base particles in an aqueous medium to obtain a toner base particle dispersion, and then add an organosilicon compound to form the convex shape, thereby obtaining a toner particle dispersion.
[0037] The toner base particle dispersion liquid is preferably adjusted to have a solids concentration of 25% by mass or more and 50% by mass or less. The temperature of the toner base particle dispersion liquid is preferably adjusted to 35° C. or more. The pH of the toner base particle dispersion liquid is preferably adjusted to a pH at which condensation of the organosilicon compound does not proceed easily. The pH at which condensation of the organosilicon compound does not proceed easily varies depending on the substance, so it is preferably adjusted within ±0.5 of the pH at which the reaction does not proceed easily.
[0038] On the other hand, it is preferable to use an organosilicon compound that has been hydrolyzed. For example, the organosilicon compound is hydrolyzed in a separate vessel as a pretreatment. The concentration of the hydrolysis is preferably 40 parts by mass or more and 500 parts by mass or less of water from which ions have been removed, such as ion-exchanged water or RO water, when the amount of the organosilicon compound is 100 parts by mass, and more preferably 100 parts by mass or more and 400 parts by mass or less of water. The hydrolysis conditions are preferably pH 2.0 or more and 7.0 or less, temperature 15°C or more and 80°C or less, and time 30 minutes or more and 600 minutes or less.
[0039] The obtained hydrolyzed liquid of the organosilicon compound is mixed with the toner base particle dispersion liquid, and the pH is adjusted to a value suitable for condensation (preferably 6.0 to 12.0, or 1.0 to 3.0, more preferably 8.0 to 12.0). The amount of the hydrolyzed liquid of the organosilicon compound is adjusted so that the amount of the organosilicon compound is 3.0 to 30.0 parts by mass per 100 parts by mass of the toner base particles, which makes it easier to form a convex shape. In forming the convex shape, it is preferable to maintain the condensation temperature at 35° C. or higher for 60 minutes or more.
[0040] From the viewpoint of controlling the convex shape of the surface of the toner particles, it is preferable to adjust the pH in two stages. The convex shape of the surface of the toner particles can be controlled by appropriately adjusting the holding time before adjusting the pH in the first stage and the holding time before adjusting the pH in the second stage to condense the organosilicon compound. The convex shape of the surface of the toner particles can also be controlled by adjusting the condensation temperature of the organic compound in the range of 35°C to 80°C and the pH value.
[0041] As an example of forming organosilicon polymer particles on the surface of the toner base particles that easily migrate to the drum side, a more preferable convex shape can be formed by further increasing the pH after forming the convex shape and then adding the organosilicon compound. The pH is preferably 10.5 or higher. By adding the organosilicon compound to the toner base particle dispersion at this pH, hydrolysis and condensation proceed rapidly while the organosilicon polymer adheres to the surface of the toner base particles. The organosilicon polymer adhered to the surface of the toner base particles in this way has a relatively low adhesive force to the toner base particles, and therefore easily migrates to the drum.
[0042] In addition, the number of convex portions X observed by cross-sectional observation of the toner by STEM is preferably 10 or more per toner particle. A large number of convex portions X provides a sufficient spacer effect and an effect of reducing electrical adhesion, so that transferability at a low transfer bias is further improved. The number of convex portions X can be controlled by the amount of organic silicon compound charged during production and the pH of the toner base particle dispersion liquid. From the viewpoint of fixability, the number of convex portions X is preferably 300 or less.
[0043] Furthermore, it is preferable that the aspect ratio of the convex portion X transferred into water by the water washing method is 0.3 or more and 0.8 or less, and the average circularity of the convex portion X transferred into water by the water washing method is 0.70 or more and 0.90 or less, as measured by a flow type image analysis method. By having an aspect ratio of 0.8 or less, rolling on the drum is suppressed, so that the toner and the convex portion X can be efficiently rubbed together, and the transferability is further improved. On the other hand, by having an aspect ratio of 0.3 or more, the fluidity is maintained, so that the transferability is further improved. By having an average circularity of 0.90 or less, rolling on the drum is suppressed, so that the toner and the convex portion X can be efficiently rubbed together, and the transferability is further improved. On the other hand, by having an average circularity of 0.70 or more, the fluidity is maintained, so that the transferability is further improved. The aspect ratio and the average circularity can be controlled by the pH, temperature, time, stirring speed, etc. of the toner particle dispersion liquid during production.
[0044] Specific methods for producing the toner of the present invention will be described below, but the methods are not limited thereto.
[0045] The toner base particles can be produced by known means, and can be produced by kneading and grinding or wet production. From the viewpoint of uniform particle size and shape controllability, the wet production method can be preferably used. Further, the wet production method can be exemplified by suspension polymerization, dissolution suspension, emulsion polymerization aggregation, emulsion aggregation, etc., and the suspension polymerization method can be preferably used in the present invention. In the suspension polymerization method, the organosilicon polymer is easily precipitated uniformly on the surface of the toner base particles, and the adhesion between the organosilicon polymer of the toner particles and the toner base particles is excellent. The toner obtained from these toner particles has good environmental stability, charge reversal component suppression effect, and durability thereof. The suspension polymerization method will be further described below.
[0046] The suspension polymerization method is a method in which a polymerizable monomer composition containing a polymerizable monomer capable of producing a binder resin and, if necessary, an additive such as a colorant is granulated in an aqueous medium, and the polymerizable monomer contained in the polymerizable monomer composition is polymerized to obtain toner base particles.
[0047] The polymerizable monomer composition may contain a release agent and other resins as necessary. After the polymerization step is completed, the generated particles are washed, collected by filtration, and dried to obtain toner base particles. The temperature may be raised in the latter half of the polymerization step. In addition, in order to remove unreacted polymerizable monomers or by-products, it is also possible to distill off a part of the dispersion medium from the reaction system in the latter half of the polymerization step or after the polymerization step is completed. The release agent may be the following: petroleum waxes such as paraffin wax, microcrystalline wax, and petrolatum and derivatives thereof, montan wax and derivatives thereof, hydrocarbon waxes and derivatives thereof by the Fischer-Tropsch method, polyolefin waxes such as polyethylene and polypropylene and derivatives thereof, natural waxes and derivatives thereof such as carnauba wax and candelilla wax, higher aliphatic alcohols, fatty acids such as stearic acid and palmitic acid, or compounds thereof, acid amide waxes, ester waxes, ketones, hydrogenated castor oil and derivatives thereof, vegetable waxes, animal waxes, and silicone resins. The derivatives include oxides, block copolymers with vinyl monomers, and graft modified products. They can be used alone or in combination.
[0048] As the other resins, the following resins can be used as long as they do not affect the effects of the present invention. Homopolymers of styrene and its substitutes such as polystyrene and polyvinyltoluene; styrene-based copolymers such as styrene-propylene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-methyl acrylate copolymer, styrene-ethyl acrylate copolymer, styrene-butyl acrylate copolymer, styrene-octyl acrylate copolymer, styrene-dimethylaminoethyl acrylate copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-butyl methacrylate copolymer, styrene-dimethylaminoethyl methacrylate copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl ethyl ether copolymer, styrene-vinyl methyl ketone copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-maleic acid copolymer, and styrene-maleic acid ester copolymer; polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resin, polyester resin, polyamide resin, epoxy resin, polyacrylic resin, rosin, modified rosin, terpene resin, phenolic resin, aliphatic or alicyclic hydrocarbon resin, and aromatic petroleum resin. They can be used alone or in combination.
[0049] Suitable examples of the polymerizable monomer in the suspension polymerization method include the vinyl polymerizable monomers shown below. Styrene; styrene derivatives such as α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octyl, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene; methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-amyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-nonyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethyl phosphate ethyl acrylate, diethyl phosphate ethyl acrylate, and dibutyl phosphate ethyl acrylate. methacrylic polymerizable monomers such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, n-nonyl methacrylate, diethyl phosphate ethyl methacrylate, and dibutyl phosphate ethyl methacrylate; methylene aliphatic monocarboxylic acid esters; vinyl esters such as vinyl acetate, vinyl propionate, vinyl benzoate, vinyl butyrate, vinyl benzoate, and vinyl formate; vinyl ethers such as vinyl methyl ether, vinyl ethyl ether, and vinyl isobutyl ether; vinyl methyl ketone, vinyl hexyl ketone, and vinyl isopropyl ketone.
[0050] Among these vinyl polymers, styrene polymers, styrene-acrylic copolymers, and styrene-methacrylic copolymers are preferred.
[0051] In addition, a polymerization initiator may be added when polymerizing the polymerizable monomer. Examples of the polymerization initiator include the following: azo-based or diazo-based polymerization initiators such as 2,2'-azobis-(2,4-divaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile; and peroxide-based polymerization initiators such as benzoyl peroxide, methyl ethyl ketone peroxide, diisopropyloxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide. These polymerization initiators are preferably added in an amount of 0.5% by mass or more and 30.0% by mass or less relative to 100 parts by mass of the polymerizable monomer, and may be used alone or in combination.
[0052] In order to control the molecular weight of the binder resin constituting the toner base particles, a chain transfer agent may be added during polymerization of the polymerizable monomer. The preferred amount of the chain transfer agent added is 0.001% by mass or more and 15,000% by mass or less with respect to 100 parts by weight of the polymerizable monomer.
[0053] On the other hand, in order to control the molecular weight of the binder resin constituting the toner mother particles, a crosslinking monomer may be added as a crosslinking agent when polymerizing the polymerizable monomer. Examples of the crosslinking monomer include: divinylbenzene, bis(4-acryloxypolyethoxyphenyl)propane, ethylene glycol diacrylate, 1,3-butylene glycol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol #200, #400, and #600 diacrylates, dipropylene glycol diacrylate, polypropylene glycol diacrylate, polyester type diacrylate (MANDA Nippon Kayaku), and those in which the above acrylates are replaced with methacrylates.
[0054] Examples of polyfunctional crosslinkable monomers include pentaerythritol triacrylate, trimethylolethane triacrylate, trimethylolpropane triacrylate, tetramethylolmethane tetraacrylate, oligoester acrylate and its methacrylate, 2,2-bis(4-methacryloxy-polyethoxyphenyl)propane, diacryl phthalate, triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, and diaryl chlorendate. The preferred amount of addition is 0.001% by mass or more and 15.000% by mass or less based on 100 parts by mass of the polymerizable monomer.
[0055] When the medium used in the suspension polymerization is an aqueous medium, the following can be used as a dispersion stabilizer for the particles of the polymerizable monomer composition: tricalcium phosphate, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silica, and alumina. Examples of organic dispersants include polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch.
[0056] Commercially available nonionic, anionic, or cationic surfactants may also be used. Examples of such surfactants include sodium dodecyl sulfate, sodium tetradecyl sulfate, sodium pentadecyl sulfate, sodium octyl sulfate, sodium oleate, sodium laurate, and potassium stearate.
[0057] The colorant used in the toner of the present invention is not particularly limited, and any known colorant can be used.
[0058] The content of the colorant is preferably 3.0 parts by mass or more and 15.0 parts by mass or less with respect to 100 parts by mass of the binder resin or polymerizable monomer.
[0059] In the toner of the present invention, a charge control agent can be used during the production of the toner, and a known charge control agent can be used. The amount of the charge control agent added is preferably 0.01 parts by mass or more and 10.00 parts by mass or less with respect to 100 parts by mass of the binder resin or polymerizable monomer.
[0060] The toner of the present invention may, if necessary, externally add various organic or inorganic fine powders to the toner particles. From the viewpoint of durability when added to the toner particles, the organic or inorganic fine powder preferably has a particle size of 1 / 10 or less of the weight average particle size of the toner particles.
[0061] As the organic or inorganic fine powder, for example, the following can be used. (1) Fluidity imparting agents: silica, alumina, titanium oxide, carbon black and carbon fluoride. (2) Abrasives: metal oxides (e.g., strontium titanate, cerium oxide, alumina, magnesium oxide, chromium oxide), nitrides (e.g., silicon nitride), carbides (e.g., silicon carbide), metal salts (e.g., calcium sulfate, barium sulfate, calcium carbonate). (3) Lubricants: Fluorine-based resin powder (e.g., vinylidene fluoride, polytetrafluoroethylene), fatty acid metal salts (e.g., zinc stearate, calcium stearate). (4) Charge control particles: metal oxides (e.g., tin oxide, titanium oxide, zinc oxide, silica, alumina), carbon black.
[0062] The organic or inorganic fine powder may be surface-treated to improve the fluidity of the toner and to make the toner uniformly charged. Examples of the treatment agent for hydrophobizing the organic or inorganic fine powder include unmodified silicone varnish, various modified silicone varnishes, unmodified silicone oil, various modified silicone oils, silane compounds, silane coupling agents, other organic silicon compounds, and organic titanium compounds. These treatment agents may be used alone or in combination.
[0063] Various measurement methods related to the present invention will be described below. <Method of observing the cross section of a toner using a scanning transmission electron microscope (STEM)> A cross section of a toner to be observed with a scanning transmission electron microscope (STEM) is prepared as follows. The procedure for preparing the cross section of the toner will be described below. First, the toner is spread onto a cover glass (Matsunami Glass Co., Ltd., square cover glass; square No. 1) to form a single layer, and then an osmium plasma coater (Filgen Co., Ltd., OPC80T) is used to apply an Os film (5 nm) and a naphthalene film (20 nm) to the toner as a protective film. Next, a PTFE tube (Φ1.5mm×Φ3mm×3mm) is filled with photocurable resin D800 (JEOL Ltd.), and the cover glass is gently placed on top of the tube so that the toner is in contact with the photocurable resin D800. In this state, the resin is hardened by irradiating it with light, and then the cover glass and tube are removed to form a cylindrical resin with the toner embedded in the outermost surface. Using an ultrasonic ultramicrotome (Leica, UC7), a cutting speed of 0.6 mm / s is used to cut from the outermost surface of the cylindrical resin to the length of the toner radius (for example, 4.0 μm when the weight average particle size (D4) is 8.0 μm) to expose a cross section of the center of the toner. Next, a thin sample of the cross section of the toner is prepared by cutting it to a thickness of 100 nm. By cutting in this manner, a cross section of the center of the toner can be obtained.
[0064] The STEM probe size was 1 nm, and the image size was 1024 × 1024 pixels. In addition, the bright-field image was acquired by adjusting the Contrast on the Detector Control panel to 1425, the Brightness to 3750, and the Contrast on the Image Control panel to 0.0, Brightness to 0.5, and Gamma to 1.00. The image magnification is 100,000 times, and the image is captured so that about one-quarter to one-half of the circumference of the cross section of one toner particle is captured, as shown in Figure 1. The obtained images are analyzed using image processing software (Image J (available from https: / / imagej.nih.gov / ij / )) and the protrusions containing the organosilicon polymer are measured. Image analysis is performed on 30 points of the STEM images.
[0065] First, use the line drawing tool (select Segmented line on the Straght tab) to draw a line along the perimeter of the toner base particle. In areas where the protruding parts of the organosilicon polymer are embedded in the toner base particle, connect the lines smoothly, assuming that they are not embedded. Using that line as a reference, convert to a horizontal image (select Selection on the Edit tab, change the line width to 500 pixels in the properties, then select Selection on the Edit tab and perform Straghtener). Select ROI Manager from Tools in the Analyze menu, and check Show All and Labels in the newly opened ROI Manager window. Next, use the straight line tool (Straight Line) on the toolbar to obtain a straight line converted from the line along the periphery of the toner base particle of the convex portion as shown in Figure 2. Draw a straight line perpendicular to that straight line and intersect with the curve of the convex portion with a maximum height H. In this state, select Add in the ROI Manager window. Next, draw a straight line perpendicular to H with a maximum width w, select Add, and then select Measure in the ROI Manager window to perform the analysis. Obtain the lengths (Length) corresponding to H and w from the newly opened Results window, and calculate H / w.
[0066] Using this calculation, the number of protrusions Y with a protrusion height H of 40 nm or more and P(H / w) of 0.33 or more and 0.80 or less is counted, and the number ratio to the entire number of protrusions Y in the 30 STEM images is calculated. When determining the number of the convex portions X observed by cross-sectional observation, an image is obtained at an image magnification of 50,000 times so that one toner particle fits therein, and the number of the convex portions X in the obtained image is counted. The number of the convex portions X is determined by counting the number of the convex portions X for 30 toner particles and averaging the result.
[0067] <Scanning Electron Microscope (SEM) Observation Method> The SEM observation method is as follows: Images taken with a Hitachi ultra-high resolution field emission scanning electron microscope S-4800 (Hitachi High-Technologies Corporation) are used. The image taking conditions for the S-4800 are as follows:
[0068] (1) Sample preparation A thin layer of conductive paste (TED PELLA, Inc., Product No. 16053, PELCO Colloidal Graphite, Isopropanol base) is applied to a sample stage (aluminum sample stage 15 mm x 6 mm), and toner is sprayed onto it. Air is then used to remove excess fine particles from the sample stage, after which platinum is evaporated at 15 mA for 15 seconds. The sample stage is set in the sample holder, and the sample stage height is adjusted to 30 mm using the sample height gauge.
[0069] (2) S-4800 observation condition setting Pour liquid nitrogen into the anti-contamination trap attached to the S-4800 housing until it overflows, and leave it for 30 minutes. Start the S-4800's "PC-SEM" and perform flushing (cleaning the FE chip, which is the electron source). Click the accelerating voltage display area on the control panel on the screen, and press the [Flushing] button to open the flushing execution dialog. Check that the flushing intensity is 2, and execute it. Check that the emission current due to flushing is 20 to 40 μA. Insert the sample holder into the sample chamber of the S-4800 housing. Press [Origin] on the control panel to move the sample holder to the observation position. Click the accelerating voltage display to open the HV setting dialog, and set the accelerating voltage to [2.0 kV] and the emission current to [10 μA]. In the [Basic] tab of the operation panel, set the signal selection to [SE], select the SE detector to [Bottom (L)], and set the mode to observe the backscattered electron image. In the same [Basic] tab of the operation panel, set the probe current in the electron optical system condition block to [Normal], the focus mode to [UHR], and the WD to [8.0 mm]. Press the [ON] button in the accelerating voltage display on the control panel to apply the accelerating voltage.
[0070] (3) Focus adjustment Drag within the magnification display on the control panel to set the magnification to 5000 (5k). Rotate the focus knob [COARSE] on the operation panel to adjust the aperture alignment once the image is in focus to a certain extent. Click [Align] on the control panel to display the alignment dialog and select [Beam]. Rotate the STIGMA / ALIGNMENT knobs (X, Y) on the operation panel to move the displayed beam to the center of the concentric circles. Next, select [Aperture] and turn the STIGMA / ALIGNMENT knobs (X,Y) one by one to stop the image movement or adjust it so that it moves as little as possible. Close the Aperture dialog and use autofocus to adjust the focus. Repeat this operation two more times to adjust the focus. With the midpoint of the maximum diameter of the observed particle aligned with the center of the measurement screen, drag within the magnification display area of the control panel to set the magnification to 10,000 (10k). Turn the focus knob [COARSE] on the operation panel until the image is in focus to a certain extent, then adjust the aperture alignment. Click [Align] on the control panel to display the alignment dialog and select [Beam]. Turn the STIGMA / ALIGNMENT knobs (X,Y) on the operation panel to move the displayed beam to the center of the concentric circles. Next, select [Aperture] and turn the STIGMA / ALIGNMENT knobs (X, Y) one by one to stop the image movement or adjust it so that the movement is minimized. Close the Aperture dialog and adjust the focus using autofocus. After that, set the magnification to 50,000 (50k) times and adjust the focus using the focus knob and STIGMA / ALIGNMENT knob as above, then use autofocus to focus again. Repeat this operation to adjust the focus.
[0071] (4) Image storage Adjust the brightness in ABC mode, then take and save a photo with a size of 640 x 480 pixels. From the obtained SEM observation results, the number average diameter (D1) of 500 convex portions having a maximum diameter of 20 nm or more that are present on the toner surface was calculated using image processing software (Image J). The measurement method is as follows.
[0072] <Method for measuring the migration rate of convex part X by water washing method> The toner is observed with an SEM before and after washing, and the number of convex parts X that is reduced after washing is counted from the number of convex parts X before washing to calculate the migration rate. Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Add 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of nonionic surfactants, anionic surfactants, and organic builders, manufactured by Wako Pure Chemical Industries, Ltd.) to a centrifuge tube (volume 50 ml) to prepare a dispersion. Add 1.0 g of toner to this dispersion and break up the toner clumps with a spatula or similar. The centrifuge tube is shaken in a shaker at 350 strokes per minute (spm) for 20 minutes. After shaking, the solution is transferred to a glass tube for a swing rotor (capacity 50 mL) and separated in a centrifuge (H-9R, manufactured by Kokusan Co., Ltd.) at 3500 rpm for 30 minutes. It is visually confirmed that the toner and the aqueous solution are sufficiently separated, and the toner separated in the uppermost layer is collected with a spatula or the like. The collected aqueous solution containing the toner is filtered with a vacuum filter and then dried in a dryer for at least one hour. The dried toner is crushed with a spatula to obtain a post-wash sample. Then, the sample before and the sample after washing are each subjected to SEM observation by the method described above. From the obtained SEM observation results, the number of convex parts X present on the toner surface is counted by color-coding the convex parts and toner base particles in the image by binarizing them with image processing software (Image J). This operation is repeated several times, and the number N of the convex portions X (total number of the convex portions X before washing) is calculated by finding the average value for 100 toner particles. The number N of the convex portions after washing is calculated in the same manner. After that, the migration rate can be calculated by the following formula. Migration rate (number%) = {N (before washing) - N (after washing)} / N (before washing)
[0073] If you want to find the migration rate in weight percent, you can do so by the following method. Measure the amount of silicon in the washed sample using fluorescent X-rays. Calculate the migration rate (weight percent) from the ratio of the amount of the measured element between the toner after washing and the toner before washing.
[0074] The measurement of fluorescent X-rays for each element conforms to JIS K 0119-1969, and specifically, is as follows. The measurement equipment used is a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical) for setting measurement conditions and analyzing measurement data. Rh is used as the anode of the X-ray tube, the measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 10 mm, and the measurement time is 10 seconds. In addition, detection is performed with a proportional counter (PC) when measuring light elements, and a scintillation counter (SC) when measuring heavy elements. For the measurement sample, about 1g of the toner after washing and the toner before washing are placed in a dedicated aluminum ring with a diameter of 10mm and flattened. Next, using a tablet molding compression machine "BRE-32" (manufactured by Maekawa Test Machinery Manufacturing Co., Ltd.), the toner is pressed at 20MPa for 60 seconds to form a pellet with a thickness of about 2mm. Measurements are performed under the above conditions, and elements are identified based on the peak positions of the obtained X-rays, and their concentrations are calculated from the counting rate (unit: cps), which is the number of X-ray photons per unit time.
[0075] The method for quantifying the amount of silicon in the toner is, for example, to add 0.5 parts by mass of silica (SiO2) fine powder to 100 parts by mass of toner particles, and thoroughly mix using a coffee mill. Similarly, 2.0 parts by mass and 5.0 parts by mass of silica fine powder are mixed with the toner particles, respectively, and these are used as samples for the calibration curve. For each sample, a pellet of the calibration curve sample is prepared as described above using a tablet press, and the count rate (unit: cps) of the Si-Kα ray observed at a diffraction angle (2θ) = 109.08° when PET is used as the analyzing crystal is measured. In this case, the acceleration voltage and current value of the X-ray generator are 24 kV and 100 mA, respectively. A linear function calibration curve is obtained by plotting the obtained X-ray count rate on the vertical axis and the amount of SiO2 added in each calibration curve sample on the horizontal axis.
[0076] Next, the toner to be analyzed is pelletized as described above using a tablet molding compressor, and the count rate of the Si-Kα radiation is measured. The content of the organosilicon polymer in the toner is then calculated from the calibration curve. The ratio of the amount of elements in the toner after washing with water to the amount of elements in the initial toner calculated by the above method is calculated and used as the migration rate (wt%).
[0077] <Method for measuring number-average particle diameters D1 and D2 of convex parts migrated into water> The number-average primary particle size is measured using a dynamic light scattering particle size distribution analyzer (Nanotrac WaveII UZ152: manufactured by Microtrack Bell Co., Ltd.). The measurement is performed by measuring the particle size of the particles contained in the aqueous solution when the toner and aqueous solution are separated using a centrifuge in the above-mentioned water washing method procedure. The mixture is adjusted to an appropriate concentration and placed in a cell, and the measurement is performed after waiting one minute to eliminate the influence of air bubbles. The measurement conditions are a sample particle refractive index of 1.59, a dispersion medium refractive index of 1.33, and a measurement time of 600 seconds, and the measurement is performed according to the procedure described in the instruction manual. The particle sizes obtained for each channel are accumulated from the smallest on a number basis, and the point where the accumulation reaches 50% is taken as the number-average primary particle size. This measurement is performed three times to obtain the average value.
[0078] <Measurement of aspect ratio and average circularity by flow type image analysis of convex part X> The measurement devices used are the flow type particle image analyzer "FPIA-3000" (Sysmex Corporation) and the "FPIA-3000 autosampler with automatic sample dispersion function" (Sysmex Corporation). The measurement conditions are set and the measurement data is analyzed using the accompanying dedicated software. For the measurement, a high-magnification imaging unit (objective lens "LUCPLFLN" (magnification 20 times, numerical aperture 0.40)) is used, and the measurement is performed after adjusting the focus using 1.0 μm polystyrene latex particles #5100A (manufactured by DUKE SCIENTIFIC CORP.). Particle sheath "PSE-900A" (manufactured by Sysmex Corporation) is used as the sheath liquid. The autosampler conditions are as follows: dispersant dispensed amount 0.5 mL, particle sheath dispensed amount 10 mL, rocking stirring intensity 80%, rocking stirring time 30 seconds, ultrasonic irradiation intensity 80%, ultrasonic irradiation time 300 seconds, propeller stirring rotation speed 500 rpm, and propeller stirring time 300 seconds. 10 ml of sample is weighed into an autosampler beaker and set in the autosampler. The measurement conditions are set to measurement mode HPF and total count number 2000. In the measurement of the present invention, the average circularity and aspect ratio are analyzed using the attached analysis software. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is in no way limited thereto. Parts used in the examples are by weight unless otherwise specified. First, a toner production example will be described.
[0080] [Toner 1 manufacturing example] (Hydrolysis process of organosilicon compounds) 60.0 parts of ion-exchanged water was weighed into a reaction vessel equipped with a stirrer and a thermometer, and the pH was adjusted to 4.0 using 10% by mass hydrochloric acid. This was heated with stirring to a temperature of 40°C. Then, 40.0 parts of methyltriethoxysilane, an organosilicon compound, was added and stirred for 2 hours or more to carry out hydrolysis. The end point of hydrolysis was confirmed by visual observation when the oil and water did not separate and became one layer, and the mixture was cooled to obtain a hydrolyzed liquid of an organosilicon compound.
[0081] (Preparation process of polymerizable monomer composition) Styrene: 60.0 parts CI Pigment Blue 15:3:6.5 parts The above materials were charged into an attritor (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and further dispersed using zirconia particles having a diameter of 1.7 mm at 220 rpm for 5.0 hours to prepare a pigment dispersion. The following materials were added to the above pigment dispersion. Styrene: 20.0 parts n-Butyl acrylate: 20.0 parts Crosslinking agent (divinylbenzene): 0.3 parts Saturated polyester resin: 5.0 parts (Polycondensation product of propylene oxide modified bisphenol A (2 mole adduct) and terephthalic acid (molar ratio 10:12), glass transition temperature Tg = 68°C, weight average molecular weight Mw = 10,000, molecular weight distribution Mw / Mn = 5.12) Fischer-Tropsch wax (melting point 78°C): 7.0 parts The mixture was kept at 65° C. and was uniformly dissolved and dispersed at 500 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to prepare a polymerizable monomer composition.
[0082] (Preparation process of aqueous medium 1) In a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, 650.0 parts of ion-exchanged water and 14.0 parts of sodium phosphate (Rasa Kogyo Co., Ltd., 12-hydrate) were added, and the mixture was kept at 65°C for 1.0 hour while purging with nitrogen. Using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), while stirring at 15,000 rpm, an aqueous calcium chloride solution in which 9.2 parts of calcium chloride (dihydrate) was dissolved in 10.0 parts of ion-exchanged water was added all at once to prepare an aqueous medium containing a dispersion stabilizer. Furthermore, 10% by mass of hydrochloric acid was added to the aqueous medium to adjust the pH to 5.0, and aqueous medium 1 was obtained.
[0083] (granulation process) While maintaining the temperature of the aqueous medium 1 at 70° C. and the rotation speed of the TK homomixer at 15,000 rpm, the polymerizable monomer composition was charged into the aqueous medium 1, and 10.0 parts of t-butyl peroxypivalate as a polymerization initiator was added. Granulation was continued for 10 minutes while maintaining the stirring speed at 15,000 rpm with the stirring device.
[0084] (Polymerization and distillation process) After the granulation step, the agitator was replaced with a propeller agitator and the mixture was stirred at 150 rpm while maintaining the temperature at 70° C. for 5.0 hours, and then the temperature was raised to 85° C. and heated for 2.0 hours to carry out the polymerization reaction. Thereafter, the slurry was heated to 100° C. and distilled for 6 hours to remove the unreacted polymerizable monomer, thereby obtaining a toner base particle dispersion liquid.
[0085] (Protrusion X Forming Process) The temperature of the obtained toner base particle dispersion liquid was cooled to 55°C, and then 25.0 parts of the hydrolyzed liquid of the organosilicon compound was added as "addition step 1" to initiate polymerization of the organosilicon compound. After holding for 15 minutes, the pH was adjusted to 5.5 with a 3.0% aqueous sodium bicarbonate solution. After holding for 60 minutes as "holding step 1" while continuing stirring at 55°C, the pH was adjusted to 9.5 with a 3.0% aqueous sodium bicarbonate solution as "pH adjustment 1", and further held for 240 minutes as "holding step 2". Furthermore, as "pH adjustment 2", the pH was adjusted to 12.0 with a 1.0 mol / L aqueous sodium hydroxide solution. Next, as "addition step 2", 8.0 parts of methyltriethoxysilane was added while continuing stirring at 55°C, and further, as "holding step 3", the mixture was held for 180 minutes to form a convex portion X. After that, the mixture was cooled to obtain a toner particle dispersion.
[0086] (Washing and drying process) After the polymerization process was completed, the toner particle dispersion was cooled, and hydrochloric acid was added to the toner particle dispersion to adjust the pH to 1.5 or less, and the dispersion was left to stand with stirring for 1 hour, after which the dispersion was subjected to solid-liquid separation using a pressure filter to obtain a toner cake. This was reslurried in ion-exchanged water to make a dispersion again, and then the dispersion was subjected to solid-liquid separation using the aforementioned filter to obtain a toner cake. The obtained toner cake was dried in a thermostatic chamber at 40° C. for 72 hours and further classified to obtain toner particles 1. In this example, the obtained toner particles 1 were used as they are as toner 1 without adding any external additives. Table 1 shows the production conditions for toner 1. The obtained toner was subjected to the measurement of various physical properties by the above-mentioned methods. Table 2 shows the measurement results of the physical properties of the produced toner 1.
[0087] [Production Examples of Toners 2 to 21 and Comparative Toners 3 to 7] The manufacturing conditions in the step of forming the protruding portion X in the manufacturing example of toner 1 were changed as shown in Table 1. Apart from that, the toner was manufactured in the same manner as in the manufacturing example of toner 1.
[0088] [Example of manufacturing comparative toner 1] In the production example of toner 1, the step of forming convex portion X was not carried out. Except for this, the toner was produced in the same manner as in the production example of toner 1. Comparative toner 1 is a toner that does not have convex portions X of an organosilicon polymer on the surface of the toner base particles.
[0089] [Example of manufacturing comparative toner 2] In the step of forming the convex portion X in the production example of toner 1, the time of the holding step 1 was set to 1440 minutes, and the subsequent pH adjustment step 1 and subsequent steps were not carried out, but the toner was cooled to obtain a toner particle dispersion. Except for this, the toner was produced in the same manner as in the production example of toner 1. Comparative toner 2 is a toner having an organosilicon polymer on the surface of the toner base particles, but not having the convex portion X.
[0090] [Table 1]
[0091] [Table 2]
[0092] <Example 1> The following evaluations were carried out on Toner 1. The evaluation results are shown in Table 3. The evaluation was carried out using a modified Canon laser beam printer LBP7600C, which is available on the market. The modification involved changing the evaluation machine itself and software to rotate the developing roller at 1.8 times the peripheral speed, setting conditions that make it easier for the roller to deteriorate over time. Specifically, the developing roller rotation speed before modification was 200mm / sec, but after modification it was changed to 360mm / sec. The transfer bias was also made adjustable. 40 g of Toner 1 was loaded into the toner cartridge of the LBP7600C. The toner cartridge was then left for 24 hours in an environment of normal temperature and humidity NN (25° C. / 50% RH). After being left for 24 hours in that environment, the toner cartridge was attached to the LBP7600C.
[0093] <Evaluation of transferability (transfer efficiency)> The transferability was evaluated by determining the transfer efficiency. The transfer efficiency is an index of transferability that indicates to what extent the toner developed on the photosensitive drum is transferred onto the intermediate transfer belt. The transferability was evaluated before and after printing out up to 4,000 sheets of A4 paper in landscape orientation with a print rate of 35.0% in an NN environment, and the change in transferability before and after durability testing was evaluated. To evaluate the transferability, a solid image was output, and the residual toner remaining on the photoreceptor during the formation of the solid image was taped off using transparent polyester adhesive tape. The density difference was calculated by subtracting the density of the paper with only the adhesive tape from the density of the paper with the removed adhesive tape. The resultant density difference was judged as follows. The density was measured using an X-Rite color reflection densitometer (X-rite 500 Series, manufactured by X-rite). A grade of C or higher was judged to be good. (Evaluation Criteria) A: The concentration difference is less than 0.05 B: Density difference is 0.05 or more and less than 0.10 C: Density difference is 0.10 or more and less than 0.240 D: Density difference is 0.240 or more
[0094] <Examples 2 to 19 and Comparative Examples 1 to 7> Evaluation was carried out in the same manner as in Example 1, except that the toners were changed to 2 to 19 and comparative toners 1 to 7. The evaluation results are shown in Table 3.
[0095] [Table 3]
[0096] As a result of the evaluation, the toner of the present invention was able to maintain excellent transferability throughout the durability test even at low transfer bias, as shown in Table 3. [Explanation of symbols]
[0097] 1 STEM image, 2 toner mother particle, 3 surface of toner mother particle, 4. A convex portion X containing an organosilicon polymer; 5. A convex portion Y having a convex height of 40 nm or more; 6 convex width w, 7 convex height H
Claims
1. A toner having a toner base particle and a toner particle having a plurality of convex portions X present on a surface of the toner base particle, the protruding portion X contains an organosilicon polymer, In cross-sectional observation of the toner using a scanning transmission electron microscope (STEM), When the maximum line segment at the continuous interface between the convex portion X and the toner base particle is defined as a convex width w, and the maximum length of the convex portion X in the normal direction of the convex width w is defined as a convex height H, and among the multiple convex portions X, a convex portion X having a convex height H of 40 nm or more is defined as a convex portion Y, the ratio P(H / w) of the number of the protrusions Y in which the ratio (H / w) of the protrusion height H to the protrusion width w is 0.33 or more and 0.80 or less is 70% or more by number with respect to the entirety of the protrusions Y; a migration rate of the protrusions X in a water washing method of the toner is 7% by number or more and 20% by number or less of the entire protrusions X before washing with water; The number average particle diameter D1 of the projections X transferred into the water by the water washing method is 30 nm or more and 300 nm or less. A toner characterized by:
2. 2. The toner according to claim 1, wherein the number of the protrusions X observed by cross-sectional observation of the toner with a scanning transmission electron microscope (STEM) is 10 or more per toner particle.
3. the number average particle diameter D1 of the projections X transferred into the water by the water washing method is 50 nm or more and 300 nm or less, When the toner after the water washing method is washed again with water, the ratio D1 / D2 of the number average particle diameter D2 of the convex portions X that migrate into water is 1.0 or more and 5.0 or less. The toner according to claim 1 or 2.
4. the aspect ratio of the protrusions X transferred into water by the water washing method, as measured by a flow image analysis method, is 0.3 or more and 0.8 or less; The average circularity of the protrusions X transferred into water by the water washing method, as determined by a flow image analysis method, is 0.70 or more and 0.90 or less. The toner according to any one of claims 1 to 3.
Citation Information
Patent Citations
Method and apparatus for determination of smoke concentrati0n
JP1977023382A
Toner, two-component developer and image forming apparatus
JP2009036980A
toner
JP2017138462A
Toner
JP2020012943A
